Performance Assessment of Solar based Air Conditioning System - Mishra, S.; Singh, S. (Journal of Scientific Research, 2022)
The conventional air-conditioning system suffers from (i) harmonic distortion at the input ac side due to extensive use of nonlinear loads and (ii) not being friendly with the environment and climate. In this paper, a conventional air conditioning system (ACS), which uses a single-phase ac supply, is replaced by a solar-powered ACS to mitigate mentioned shortcomings. Due to the non-availability of solar energy during night/low-intensity levels, a battery and a dc-dc converter are used to maintain constant voltage, a prime requirement for ACS. Further, if an ac supply is used during the daytime, the battery is not required. Thus, a self-sustained solar-powered air conditioner of a capacity of 1.5 tons is designed here. The solar system is designed using Simulink, and various parameters such as torque and speed are being measured to study & analyze the solar-based ACS. The designed air conditioner gives an acceptable performance despite the variation of solar irradiations.